Eating, jigging or watching? Ocean heritage and sustainable development - Neilson, Alison; Gabriel, Rosalina; Arroz, Ana Margarida Moura; Pereira, Enésima (Green Lines Institute, 2010)
Proceedings of the 2nd International Conference on Heritage and Sustainable Development. Évora, Portugal, 22-26 June. This work emerges from the perspective that research has implications which can serve or hinder environmental and social justice within sustainable development. Who we listen to and how we listen are important to what narratives are highlighted through research. This study involves local residents as well as international tourists and people in the marine tourism industry and marine sciences in the Azores, Portugal in comparison with Newfoundland, Canada. The researchers dance between stepping out of the way in order to make room for voices and perspectives often ignored or silenced in educational and tourism stories of whales and the ocean, and stepping in to help uncover otherwise hidden forces of imperialism, and other oppressions. This study about perceptions of the ocean explores whose expression of heritage provides the driving force for commerce, business, leisure and politics. It also looks at the dynamic nature of heritage as it responds to changes in work, play and politics. Using various interview techniques including photo elicitation and focus groups, we gather rich narratives of visiting, living near and working in the sea. Multiple frames of lived experiences, ethics and politics support the narratives told. Some frames support the perceptions of diverse groups of people, while others privilege the stories of only a few. This study explores local power dynamics and global forces by asking about the ways in which people have learned about the ocean as well as how people decide what is relevant to their learning and what is important to sustain.